2011
DOI: 10.1016/j.ajpath.2011.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Dominant Negative Peroxisome Proliferator-Activated Receptor-γ (PPARγ) in Alveolar Type II Epithelial Cells Causes Inflammation and T-Cell Suppression in the Lung

Abstract: In previous work, we demonstrated that neutral lipids are essential to maintaining alveolar homeostasis. Blockage of cholesteryl ester and triglyceride metabolism in the lysosomal acid lipase (LAL) knockout mouse model resulted in heterogeneous phenotypes in the lung, including hypercellularity and emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Furthermore, we have demonstrated that the mice used in this study do not display spontaneous, progressive airspace enlargement or emphysema (69). Consistent with our results, expression of a dominant-negative mutant form of PPAR␥ in the lung epithelium of mice results in chronic inflammation and airspace enlargement (88). The relevance of this dominant-negative model is not entirely clear, since deficiency in conditionally targeted mice does not result in chronic inflammation in the absence of a "second hit" such as continuous exposure to CS.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, we have demonstrated that the mice used in this study do not display spontaneous, progressive airspace enlargement or emphysema (69). Consistent with our results, expression of a dominant-negative mutant form of PPAR␥ in the lung epithelium of mice results in chronic inflammation and airspace enlargement (88). The relevance of this dominant-negative model is not entirely clear, since deficiency in conditionally targeted mice does not result in chronic inflammation in the absence of a "second hit" such as continuous exposure to CS.…”
Section: Discussionsupporting
confidence: 76%
“…In this system, a previously established c-fms-rtTA-transgenic mouse line 9 and a (TetO) 7 -CMV-dnPPAR␥-transgenic mouse line 22 were crossbred. To assess the effect of overexpression of dnPPAR␥ on progenitor populations, the BM cells from c-fms-rtTA/(TetO) 7 -CMV-dnPPAR␥-bitransgenic mice treated with doxycycline for 3 months were analyzed for the percentage and total cell numbers of IL- 24 Overexpression of dnPPAR␥ resulted in significant increase in the percentages of LSK, LK, CMP, and GMP progenitors from doxycycline-treated bitransgenic mice compared with untreated mice (Figure 1).…”
Section: Overexpression Of Dnppar␥ Alters Hematopoietic Progenitor Pomentioning
confidence: 99%
“…The putative PPARE sites within the promoters of Api6, IL-1␤, IL-6, MMP12, and TNF-␣ were identified as described previously. 22 An anti-Flag polyclonal Ab was used to immunoprecipitate the dnPPAR␥-Flag/DNA complex. In doxycycline-treated mice, Flag-tagged dnPPAR␥ was detected bound to the promoters of the Api6, IL-1␤, IL-6, MMP12, and TNF-␣ genes by quantitative real-time PCR analysis ( Figure 3A).…”
Section: Dnppar␥ Has a Dominant-negative Effect On Pro-inflammatory Gmentioning
confidence: 99%
See 1 more Smart Citation
“…FACS analysis of CD11b, Gr-1, CD3 and B220 cells was the same as previously described [24,25]. FACS analysis of Stat3C-Flag fusion protein was analyzed by monoclonal ANTI-FLAG ® M2-FITC antibody (F4049; Sigma, Saint Louis, MI).…”
Section: Facs Analysesmentioning
confidence: 99%